The Overview of Adolescents Knowledge Level About The Dangers of Electronic Cigarettes for Healthy at Bhinneka Karya Surakarta Vocational High School - Fihudha, Ganis Dina; Sari, Irma Mustika (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Smoking has become a familiar habit, especially among teenagers. Youths are more likely to use cigarettes at a young age without regard for the potential consequences and their lack of self-awareness and therefore pay no attention to the dangers of their use. Early on in an attempt to reduce the tobacco epidemic. Knowledge of the dangers of electronic cigarettes is little known to young people, and the lack of exposure to teenagers on electronic cigarettes can cause it. This research aims to get an overview of the level of adolescent knowledge about the dangers of electronic cigarettes in health in Bhinneka Karya Surakarta Vocational High School. In the study, the method used is quantitative descriptive with a total of 75 respondents and stratified random sampling sampling taken. The instruments used were questionnaires. The results of 75 teenagers fall largely in the adequately known category of the dangers of electronic cigarettes: 42 (56.0%), 30 (40.0%) fall in the less category, and only 3 (4.0%) in the good category. It could be concluded that the level of teen knowledge about the dangers of electronic cigarettes in Bhinneka Karya Surakarta Vocational High School is adequate.